The impact of locus of control on somatic and psychological profiles of patients with irritable bowel syndrome engaging in aerobic exercise - Laura Prospero; Giuseppe Riezzo; Benedetta D’Attoma; Antonia Ignazzi; Antonella Bianco; Isabella Franco; Ritanna Curci; Angelo Campanella; Claudia Beatrice Bagnato; Piero Porcelli; Gianluigi Giannelli; Francesco Russo (Scientific Reports)
Abstract Irritable bowel syndrome (IBS) is a chronic and recurrent disorder characterized by gastrointestinal (GI) symptoms and psychological disorders. Individuals with an external locus of control (LoC), a personality trait influencing one’s actions and outcomes, are more vulnerable to IBS. Physical activity can deal with GI symptoms, preserving mental and physical health. In this context, our study aimed to investigate differences in symptom and psychological profiles among IBS patients classified by internal or external LoC when patients engaged in an aerobic exercise program (AEP). Each IBS patient was administered the International Physical Activity Questionnaire—Short Form (IPAQ-SF) before treatment, and the Physical Capacity Assessment Tests were applied before and after treatment. Participants filled out a GI symptom questionnaire before and after the intervention and some validated psychological tests to evaluate the changes induced by AEP. The AEP consisted of 180 min of moderate-intensity aerobic walking activity a week. Fifty-four IBS patients completed the 12-week study; 37 belonged to the internal LoC group and 17 to the external one. The internal LoC subgroup had a higher percentage of physically active subjects and a better physical capacity at baseline than those with external LoC. Only patients with an internal LoC achieved a statistically significant increase in physical capacity as the effect of the AEP. However, there was no statistically significant difference when Delta was considered. The somatic and psychological health status of IBS patients in the external LoC group was poorer than that of the internal LoC group at the baseline, particularly abdominal pain, psychosocial functioning, and emotional distress. After AEP, patients showed significant improvement in scores on the IBS-related and psychological scales, regardless of whether they belonged to the external or internal LoC. The present study confirmed the importance of considering both the GI symptoms and the psychological profile when dealing with IBS. AEP organized in walking groups has shown significant improvements for all IBS patients. Since external LoC was associated with poorer health status, individually tailored interventions should be planned to increase patients’ self-motivation to treatment. Trial registration: registration number NCT05453084. First Posted Date 12/07/2022.